2011
DOI: 10.1038/bjc.2011.383
|View full text |Cite
|
Sign up to set email alerts
|

BRCA2 is a moderate penetrance gene contributing to young-onset prostate cancer: implications for genetic testing in prostate cancer patients

Abstract: Background:A family history of prostate cancer (PrCa) is a strong risk factor for the disease, indicating that inherited factors are important in this disease. We previously estimated that about 2% of PrCa cases diagnosed ⩽55 years harbour a BRCA2 mutation and PrCa among BRCA2 carriers has been shown to be more aggressive, with poorer survival.Methods:To further evaluate the role of BRCA2 in PrCa predisposition, we screened 1864 men with PrCa aged between 36 and 88 years. We analysed the BRCA2 gene using a nov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
260
2
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 344 publications
(283 citation statements)
references
References 25 publications
14
260
2
7
Order By: Relevance
“…Johannesdottir et al 87 reported that this mutation was present in 2.7% of unselected Icelandic patients diagnosed with PCa at age f65 years. This prevalence is double the prevalence of germline BRCA2 mutations reported by Kote-Jarai et al 23 and Agalliu et al 22 in two cohorts of PCa patients diagnosed at age f65 years (1.2% and 0.78%, respectively). In these latter two studies, patients were screened for any 22 mutation, not only the founder ones.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…Johannesdottir et al 87 reported that this mutation was present in 2.7% of unselected Icelandic patients diagnosed with PCa at age f65 years. This prevalence is double the prevalence of germline BRCA2 mutations reported by Kote-Jarai et al 23 and Agalliu et al 22 in two cohorts of PCa patients diagnosed at age f65 years (1.2% and 0.78%, respectively). In these latter two studies, patients were screened for any 22 mutation, not only the founder ones.…”
Section: Discussionmentioning
confidence: 60%
“…23,24,51,[68][69][70][71][72][73] However, one of the challenges of studies analysing the susceptibility of PCa in BRCA mutation carriers is the low incidence of germline mutations in those genes in the general population which is estimated to be between 0.07% and 0.24% in different studies, 72,[74][75][76] and therefore, results have often been inconsistent. The ethnic population that has more extensively been studied is the Ashkenazim Jewish, due to the relative high incidence of three founder mutations (BRCA1 185delA, BRCA1 5382insC and BRCA2 6174delT).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations